Information Technology, Organizational Culture, and Service Quality: The mediating effect of Personnel’s Performance - Palma Fitria Fahlevi; Sitorus, Tigor (Technium Social Sciences Journal, 2020)
Purpose: This study aims to investigate and develop a model of empirical research on Information Technology, Organizational Culture and Personnel’s Performance to Service Quality by proposing Personnel’s Performance as a mediating variable. Design/methodology/approach:The study was conducted by surveying 100 police officers and 100 community Personnel at the join operation office between Police with Local Government of Bandung city (“Samsat”), and the data were analyzed by structural equation model, using Smart PLS. Finding: The paper finds that all hypotheses are accepted and the result of the study proves that personnel’s performance with indicators; effectiveness and efficiency, authority and responsibility, discipline, initiative, acts as an intervening variable on the influence of Information Technology and Organizational Culture toward Service Quality. Research limitations/implications: Future research should be conducted to examine the influence of all personnel performance of Indonesian Police in all join operation office between police with local government in order obtained more varied result. Besides the variables should be developed to examine the influence factors of Service quality such as; management knowledge and others. Practical implications: The proposed of information technology and organizational culture with the high loading factors which are related to increase Personnel’s Performance may help in increasing Service Quality. Both indicators could be increased together in order Personnel’s Performance be increased and impacted to service quality. Originality/value: The value of this paper as the strengthen is the model empirical research that redesign of Personnel’s Performance as mediate variables with more indicators that has high loading factor and significant value, so the Personnel’s Performance may act as mediate variable between exogenous with endogenous variable.